Real object use facilitates object recognition in semantic agnosia. - Morady, K; Humphreys, G (2009)
In the present paper we show that, in patients with poor semantic representations, the naming of real objects can improve when naming takes place after patients have been asked to use the objects, compared with when they name the objects either from vision or from touch alone, or together. In addition, the patients were strongly affected by action when required to name objects that were used correctly or incorrectly by the examiner. The data suggest that actions can be cued directly from sensory-motor associations, and that patients can then name on the basis of the evoked action.